Multi-Objective Optimization Analysis of Structural Design for Large Cooling Towers. Issue 11 (13th August 2017) - Zhao, Lin; Chen, Xu; Liang, Yuwen; Ge, Yaojun; Sun, Wen; Li, Yinan; Huang, Shikui; He, Jiantao; Li, Yingtao
ABSTRACT: Equivalent static wind loads (ESWLs) on cooling towers derived even by the refined multiple-mode dynamic algorithm such as the complete quadratic combination theory usually shows quite different types for various design targets. So, it is evitable to bring complex and burdensome calculation for structural design. To this problem, the improved multi-objectives ESWLs method was proposed by combining the wind vibration characteristics of large cooling towers itself. Through several numerical examples, the multi-objective ESWLs distribution characteristics were discussed, and its rationality of application in the cooling towers was also validated.